Group 4 permethylindenyl complexes for slurry-phase polymerisation of ethylene - Lamb, J; Buffet, J; Turner, Z; O'Hare, D (Royal Society of Chemistry, 2019)
A series of ten well-defined group 4 ansa-bridged permethylindenyl complexes have been prepared, fully characterised and supported on inorganic solid supports. These catalysts were investigated in the slurry-phase polymerisation of ethylene. A range of inorganic solid supports have been utilised; solid polymethylaluminoxane (sMAO), MAO modified layered double hydroxide (LDHMAO) and MAO modified silica (SSMAO). The sMAO supported catalytic systems exhibit some of the highest slurry-phase polymerisation activities reported in literature with activities reaching 9509 kg PE mol M-1 h -1 bar -1 for Me2 SB(Cp Me ,I∗)ZrMe 2 at 80 °C after 5 minutes of polymerisation; 34% more active than an industrial standard under similar conditions. These systems produce polyethylenes with low molecular weights, M w , reaching as low as 46 kg mol -1 for E- Me2 SB(Cp nBu ,I∗)ZrCl 2 at 90 °C after 30 minutes of polymerisation with a uniform, mono-disperse "popcorn" morphology. The sMAO supported systems show much higher catalytic activities and much more industrially desirable polyethylene morphology than the same complexes supported on LDHMAO and SSMAO.